2016
DOI: 10.1109/tro.2016.2596768
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Action Control: Closed-Form Optimal Control for Nonlinear and Nonsmooth Systems

Abstract: This paper presents a new model-based algorithm that computes predictive optimal controls on-line and in closed loop for traditionally challenging nonlinear systems. Examples demonstrate the same algorithm controlling hybrid impulsive, underactuated, and constrained systems using only high-level models and trajectory goals. Rather than iteratively optimize finite horizon control sequences to minimize an objective, this paper derives a closed-form expression for individual control actions, i.e., control values … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(107 citation statements)
references
References 66 publications
(197 reference statements)
1
106
0
Order By: Relevance
“…A model predictive controller (MPC) similar to [18] is used. However, any model predictive controller that is capable of completing the task can be used.…”
Section: B Model Predictive Controlmentioning
confidence: 99%
“…A model predictive controller (MPC) similar to [18] is used. However, any model predictive controller that is capable of completing the task can be used.…”
Section: B Model Predictive Controlmentioning
confidence: 99%
“…. , m} (see [9] for proof). By iterating on this process (Section II-A until Section II-D), SAC rapidly synthesizes piecewisecontinuous, constrained control laws for nonlinear systems.…”
Section: Decide How Long To Actmentioning
confidence: 99%
“…If the inner product is positive and the angle between the two vectors is small enough, the noise vector should move the system towards the desired control direction. The controller/filter we use is a recently formulated algorithm for control of nonlinear systems called sequential action control (SAC) presented in [9], [10], [11] and summarized in Section II. Nevertheless, it must be noted that the implementation of this method is not SAC-specific; any controller that can successfully control the system of interest can be used instead.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When measured up against its alternatives, it is observed that SAC computes higher bandwidth (1 KHz) closed-loop trajectories at a lower final cost in lesser time (milliseconds/seconds versus hours). Therefore, it can be concluded that SAC provides a model-based response to state capably even for saturated, underactuated, nonlinear, and high dimensional systems [8,9].…”
Section: Introductionmentioning
confidence: 98%